The Twelve Prophets - Segal, Michael; Ṭalmon, Shemaryahu (כתבי מפעל המקרא, 2024)
The Twelve Prophets volume of the the Hebrew University Bible Project presents a diplomatic editio maior of the text of the Hebrew Bible, based upon the Aleppo Codex, with variants from other textual testaments recorded in a system of apparatuses. The readings collated in the edition are culled from a broad variety of sources, including the ancient translations (Greek Septuagint and revisions, Latin Vulgate, Syriac Peshitta, Aramaic Targum Jonathan), Dead Sea Scrolls, biblical quotations in rabbinic literature, Genizah fragments, a broad array of medieval Hebrew manuscripts representing the Masoretic text, up to Jacob Ben-Hayyim’s Second Biblia Rabbinica of 1524-25. This extensive documentation reflects the attested transmission history of the biblical text, covering a period of almost two millennia